Peningkatan Keterampilan Guru dalam Mengajar Melalui Implementasi Supervisi Klinis - Timur Timur (Jurnal Pendidikan Dasar, 2021)
The purpose of this research is increasing the teachers’ of 2 Kajar GeneralElementary School, Sub District of Gunem, Regency of Rembang skills on teaching on 1stSemester 2019/2020 Year Academic. The design of this research is a School Action Research(SAR) with Kemmis and Mc Taggart model’s. The place of this research is 2 Kajar GeneralElementary School, Sub District of Gunem, Regency of Rembang. The time of this research isfour months: from August up to November 2019. The subjects of this research are threeteachers; Teacher of IV Grade, V Grade and VI Grade. The object of this research is theteachers’ skills on teaching. The techniqu of analyzing data of this research is descriptiveanalyzing. The result of this research is the teachers’ of 2 Kajar General Elementary School,Sub District of Gunem, Regency of Rembang skills on teaching on 1st Semester 2019/2020Year Academic increased from poor category into good category.